UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI MELALUI METODE BERMAIN DENGAN MEDIA PAPAN KREATIF - Ida Inurwati (Institut Agama Islam Negeri Metro, 2020)
This study aims to apply the playing method with creative board media to improve early childhood cognitive abilities. The research was conducted in group B TK Al Fatah Sedan. The research procedure consisted of planning, implementing, observing and reflecting. The method used in this research is Classroom Action Research (CAR), the results of the study are presented and analyzed descriptively quantitatively. Based on the results of the study, the creative board playing method was able to improve early childhood cognitive abilities with an increase in each cycle, namely the children's understanding ability reached 50% in cycle I, 65% in cycle II, and 85% in cycle III. The conclusion of this study is the method of playing with creative board media can improve early childhood cognitive abilities. Keywords: Cognitive Improvement, Playing Method, Creative Board